Rheological and anti-microbial study of silica and silver nanoparticles-reinforced k-carrageenan/hydroxyethyl cellulose composites for food packaging applications - Rukmanikrishnan, Balasubramanian; Ramalingam, Srinivasan; Kim, Sam Soo; Lee, Jaewoong (Cellulose (London), 2021)
Sustainable food packaging films were developed using a combination of k-Carrageenan (k-C), hydroxyl ethyl cellulose (HEC), silicon dioxide (SiO 2 ), and silver (Ag) nanoparticles. The CH-SiO 2 /Ag nanocomposites showed promising results, mainly due to their transparency, flexibility, low cost, and environmental friendliness. The structure and uniform morphology of the CH-SiO 2 /Ag nanocomposites were determined by FT-IR, XRD, and SEM analysis. Barrier properties (water vapor permeability-WVP), thermal properties (T 5% loss, char yield), and mechanical properties determined for the k-C/HEC and k-C/HEC-SiO 2 /Ag nanocomposites, which improved by 3.3–1.9 × 10 −9 gm/m 2 Pa s (WVP), 59.1–115.7 °C (T 5% ), 13.4–29.3% (char yield), 23.8–41.5 MPa (tensile strength), and 22.3–28.9 (EB), respectively. The contact angle of the k-C/HEC-SiO 2 /Ag nanocomposites were in the range of 60.1°–76.4°. The UV transmittance of the k-C/HEC composites decreased with the addition of SiO 2 and Ag nanoparticles. However, the transparency of the composites was not affected, and it inhibited UVA and UVB rays by the addition of Ag nanoparticles. The viscosity of the k-C/HEC composites increased with the SiO 2 content and decreased with the shear rate. All the composites exhibited shear-thinning behavior. The storage modulus of the prepared composites is higher than the loss modulus in the entire frequency region. Overall, SiO 2 and Ag nanoparticles improved the hydrophobic nature of the k-C/HEC-SiO 2 /Ag films and showed significant activity against six common food pathogens, Staphylococcus aureus, Bacillus cereus, Listeria monocytogenes, Bacillus subtilis, Salmonella typhi, and Cronobacter sakazakii . The synergistic combination of k-C/HEC-SiO 2 /Ag nanocomposite has potential candidate for packaging and other biomedical applications.